(6) \( 5^{2+x}-5^{x}=5^{x} \cdot 23+1 \)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Mind Expander
To solve the equation \( 5^{2+x}-5^{x}=5^{x} \cdot 23+1 \), let’s start by making a substitution. Let \( y = 5^x \). Then, we can rewrite \( 5^{2+x} \) as \( 5^2 \cdot 5^x \) or \( 25y \). Now the equation becomes: \[ 25y - y = 23y + 1 \] This simplifies to: \[ 24y = 23y + 1 \] Subtracting \( 23y \) from both sides: \[ y = 1 \] Recalling our substitution \( y = 5^x \), we have: \[ 5^x = 1 \] This implies: \[ x = 0 \] Therefore, the solution to the equation is: \[ \boxed{0} \]